The Role of Synthetic Root Exudates in Modulating Soil Hydraulic Properties and Strengths Under Temperature Variations - Bindeliya; Zhang, Wencan; Li, Haigang (Water (Basel), 2025)
Root exudates play a crucial role in shaping rhizosphere soil structure, water dynamics, and adaptation to environmental stress. This study investigated the effects of environmental temperature (5 °C, 15 °C, and 25 °C) on water retention and soil strength in rhizosphere versus non-rhizosphere soils, simulated by adding glucose or deionized water to soil samples. Over a 10-day drying period, changes in soil water content, evaporation rate, water repellency, penetration resistance, and unconfined compressive strength were measured. The results showed that simulated root exudates significantly enhanced water retention at 15 °C (by 21.5%), but this effect diminished at 25 °C (to 8.3%) and was negative at 5 °C (by −8.9%). Additionally, root exudates improved soil mechanical stability, with the effect being more pronounced at higher temperatures. These changes were attributed to increased organic carbon decomposition and a higher proportion of micropores (<100 μm). These findings highlight the temperature-dependent role of root exudates in regulating soil properties, with implications for agricultural management and ecosystem resilience under climate change.